Boyle Lecture 2025—Science, Technology, Theology, and Spirituality: A Necessary Partnership? - Jackelén, Antje (Zygon, 2025)
The 2025 Boyle Lecture explores the partnership between science, technology, theology, and spirituality in addressing contemporary challenges. Reflecting on historical and modern dynamics, it emphasizes the need for transdisciplinary collaboration to avoid cultural poverty and handle the current polycrisis in a world prone to polarization, populism, protectionism, post-truth, and patriarchy. The lecture offers a brief sketch of the development of the science-and-religion field and underlines the importance of including spiritual perspectives in the discourse. Drawing on Sigmund Freud, the author describes the impact of artificial intelligence on humanity as a fourth narcissistic insult and discusses four alternative approaches to this new existential threat. Two examples of the added value of including spirituality in science and religion are provided: healing the injustices of colonialism by bringing together neuroscience and theology with religious symbols, rituals, and narratives; and dealing with the climate crisis more holistically by including spiritual sustainability alongside ecological, economic, and social dimensions. The lecture concludes by describing a spirituality of hope.